ORIENTASI PEMIKIRAN PSIKOLOGI ISLAM PERSPEKTIF HISTORIS - Sri Haryanto (Manarul Qur'an: Jurnal Ilmiah Studi Islam, 2019)
This research will examine the points of psychological thought put forward by Muslim scientists in the Middle Ages, which to this day become an adjudication for the study and study of the concept of psychology in Islam. Islamic psychology is a pattern of psychology that tries to formulate the principles of human psychology from the main source of Islam (the Qur'an). Islamic psychology in its study is different from modern western psychology, which studies humans limited to the physical, psychic, and socio-cultural dimensions. Islamic psychology in addition to studying the three dimensions of man above also examines the spiritual dimension of man, which has not been touched in the study of modern psychology. Islamic psychology comes from the Qur'an which in its development was studied by Muslim scientists from Abu Zaid, al-Kindi, al-Farabi, Miskawih, Ibn Sina, al-Ghazali and others. The thought of Muslim scientists about psychology is still an adjudication of Islamic psychology studies.